The demand for and impacts of government housing: Evidence from Ethiopian lotteries - Simon Franklin (Queen Mary University of London, School of Economics and Finance, 2025)
The case for government supply of housing hinges on two key questions: do intended beneficiaries value it more than the cost to the state of providing it, and does relocation to remote housing sites impose unintended costs for movers or society? I study a large-scale lottery in Addis Ababa, Ethiopia, which randomly assigned slum residents to housing on the city's outskirts. Leveraging eight years of low-attrition panel survey data alongside market rents, construction costs, and land values, I find that willingness to pay exceeds per-unit production costs for a substantial share of slum households. There is no evidence that housing negatively affects labour market outcomes, education, or household consumption - suggesting that there are neither unanticipated drawbacks for movers nor broader negative externalities. Multiple surveys allow me to track how households adjust to moves and how new mega-neighbourhoods evolve. Although social networks and neighbourhood amenities initially deteriorate for winners, they significantly improve after 8 years. The results differ significantly by randomly assigned location, implying a weaker case for centrally located housing given its higher cost relative to benefits.
Keywords: 330; Soziale Wohnungspolitik; Nachbarschaft; Theorie; Äthiopien